Thermal comfort in temporary shelters using the Pop-up method: Case of San Martín, Perú - Gonzáles Garay, Jhon Harol (2025)
The designs of temporary shelters are essential for the Sustainable Development Goals (SDGs), 6 promoting accessible, protective, sustainable, and resilient urban developments. This applied 7 research, with a mixed-method approach and a sequential explanatory design (DEXPLIS), 8 surveyed 28 architects and interviewed five professionals from National Civil Defense Institute 9 (INDECI), Regional Emergency Operations Center (COER), Local Emergency Operations 10 Center (COEL), Peruvian General Volunteer Fire Department (CGBVP) and Peruvian National 11 Police (PNP) to optimize the design of foldable shelters inspired by origami. The proposal was 12 implemented through an interactive action-reflection cycle, evaluating actions, observing 13 impacts, and making continuous adjustments. The results revealed a low correlation between 14 the technical, spatial, and technological characteristics of the shelters and their ability to provide 15 thermal comfort. Moreover, officials indicated that in Peru, installation speed and low cost are 16 prioritized over thermal efficiency in temporary shelter design. This suggests that improving 17 designs using the POP-UP method optimizes thermal conditions and enhances the well-being 18 of affected individuals